The roles of land use planning in sustaining natural resources - Asmawi, M. Zainora; Ahmad Azam, Nur Nabila; Yahya, Nurul Hidayah; Myint, Khin Cho (2011)
The concept of sustainable development has become very important item across the world, covering many disciplines. Land use planning, among others, is challenged to play an active role in obtaining sustainable natural resources. The main focus of this paper is to study the roles played by land use planning in sustaining the natural resources. Therefore, this paper includes the study on the roles of land use via development planning system and development control decision which are to plan and to control the development. However, land use planning is not retrospective and essentially only deals with proposals to change land use, it relies on various stakeholders such as owners or land managers to initiate such changes. The practice of land use planning involves achieving a balance between the community’s environmental, social and economic needs and demands; between the rights of private property owners, the role and willingness of government at various levels to set policy and direction, and the right of the community to have input into the policy formed and decisions made. Thus, this paper highlights the significant roles played by planners in preserving the assets of Mother Nature in a sustainable manner.